OPTIMIZATION OF MULTIPLE-LOCUS VARIABLE-NUMBER TANDEM-REPEAT ANALYSIS FOR BACILLUS ANTRACIS GENOTYPING - Shevtsov, A.B.; Lutsay , V.B.; Kairzhanova , A.D.; Lukhnova , L.Yu.; Kulatay , T. Zh.; Izbanova , U.A.; Karibaev , T.B.; Shustov , A.V. (Eurasian Journal of Applied Biotechnology, 2019)
Bacillus anthracis is the causative agent of anthrax, a highly dangerous human and veterinary disease. B. anthracis has high pathogenicity, resulting in a high mortality rate, with possible long-term preservation of the live pathogen in environmental conditions. Thus, genotyping of circulating B. anthracis strains is an integral part of epidemiological surveillance worldwide. Multiple-locus variable-number tandem repeat (VNTR) analysis (MLVA) is a highly discriminatory method for genotyping bacterial species with a conserved genome such as B. anthracis. Although there is already a well-established MLVA typing scheme, protocol optimization and verification of the results are required in certain cases. This paper presents the results of optimization of the MLVA-31 protocol, which was verified in four B. anthracis strains that were isolated in Kazakhstan. The actual VNTR repeat sizes differed from those obtained by capillary electrophoresis at all VNTR loci. Moreover, absence of B. anthracis reference strains made allele identification difficult for 90% of the loci. In six loci, the actual sizes differed by one or more VNTRs from the sizes defined by capillary electrophoresis. These results indicate that availability of B. anthracis reference strains will allow for verification of genotyping results, regardless of the particular reagents and equipment used for capillary electrophoresis, thus enabling more efficient epidemiological monitoring at the local and global levels.